قرآنی قصص میں علم بیان کی معنویت: آدم، ہود، اور صالح علیہم السلام کے قصص کا تجزیاتی مطالعہ (Al-Qamar, 2024)
The rhetorical aspect of the Holy Quran is dominated in conveying its message. The Quran presents its teaching in various forms and one of its distinctive features is to narrate stories. People are always attracted towards stories as they learn life lessons from them. The Quran also uses this method and engages its reader by narrating historical incidences of different prophets and nations.  These stories definitely provide different lessons to the reader which are important for the character building of an individual. Besides this, another characteristic of the Quranic narrations is uniqueness in its eloquence, literary and linguistic style. This article aims to discuss the rhetorical features of the Quranic stories in depth. The Quranic linguistic miracles encompass similes, metaphors, lexical cohesion, tropes, appropriate usage of different expressions, synonyms and antonyms, pragmatic coherence, repetition of words and thematic sequence etc. An individual can observe that linguistic excellence is prominent in the Quranic narrations. This article sheds light on some of the aspects of ilm al bayan in the stories and this demonstrates the miraculous nature of the Quranic Discourse. It proves that the miracle of the Quran is inimitable as no one succeeded to accept the challenge of producing something like Divine Word which possesses clarity of message and eloquence simultaneously.
Keywords: Quran; stories; Rhetorical; lessons; eloquence